Time-dependent mechanical behavior of human amnion: Macroscopic and microscopic characterization - Mauri, Arabella; Perrini, Michela; Ehret, Alexander E.; De Focatiis, Davide S.A.; Mazza, Edoardo (Elsevier, 2015)
Characterizing the mechanical response of the human amnion is essential to understand and to eventually prevent premature rupture of fetal membranes. In this study, a large set of macroscopic and microscopic mechanical tests have been carried out on fresh unfixed amnion to gain insight into the time-dependent material response and the underlying mechanisms. Creep and relaxation responses of amnion were characterized in macroscopic uniaxial tension, biaxial tension and inflation configurations. For the first time, these experiments were complemented by microstructural information from nonlinear laser scanning microscopy performed during in situ uniaxial relaxation tests. The amnion showed large tension reduction during relaxation and small inelastic strain accumulation in creep. The short-term relaxation response was related to a concomitant in-plane and out-of-plane contraction, and was dependent on the testing configuration. The microscopic investigation revealed a large volume reduction at the beginning, but no change of volume was measured long-term during relaxation. Tension–strain curves normalized with respect to the maximum strain were highly repeatable in all configurations and allowed the quantification of corresponding characteristic parameters. The present data indicate that dissipative behavior of human amnion is related to two mechanisms: (i) volume reduction due to water outflow (up to ∼20 s) and (ii) long-term dissipative behavior without macroscopic deformation and no systematic global reorientation of collagen fibers.